2015
DOI: 10.1002/sres.2371
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Systems Thinking and the New Ecological Paradigm

Abstract: The goal of the present research was to examine the relationship between the cognitive paradigm systems thinking and an ecologically informed worldview, specifically the New Ecological Paradigm. One hundred and fifteen psychology undergraduate students completed an online questionnaire assessing systems thinking, ecological worldview, environmental value-orientation, connectivity to nature, and environmental behaviors. Results demonstrated that systems thinkers possess a stronger ecological worldview and sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 40 publications
8
94
1
Order By: Relevance
“…We define systems thinking as a cognitive paradigm with which people come to perceive themselves and the world to be dynamic entities that display continually emerging patterns arising from the interactions among many interdependent connecting components. Thus, systems thinking is conceptualized as a worldview that encompasses core beliefs, values and assumptions concerning reality and guides personal or societal philosophies and epistemologies (Davis and Stroink, ). In this worldview, systems thinkers possess a mindset that is more holistic than reductionist, possess an expanded understanding of causality and recognize that systems undergo constant change.…”
Section: Systems Thinking In the Literaturementioning
confidence: 77%
See 1 more Smart Citation
“…We define systems thinking as a cognitive paradigm with which people come to perceive themselves and the world to be dynamic entities that display continually emerging patterns arising from the interactions among many interdependent connecting components. Thus, systems thinking is conceptualized as a worldview that encompasses core beliefs, values and assumptions concerning reality and guides personal or societal philosophies and epistemologies (Davis and Stroink, ). In this worldview, systems thinkers possess a mindset that is more holistic than reductionist, possess an expanded understanding of causality and recognize that systems undergo constant change.…”
Section: Systems Thinking In the Literaturementioning
confidence: 77%
“…Thus, there appears to be a growing interest in the psychology of systems thinking (Davis and Stroink, ; Thibodeau et al, ) but only a small number of publications to date. As a result, the primary purpose of this paper is to delve deeper into systems thinking as a psychological construct and to explore how it operates as a cognitive paradigm.…”
Section: Systems Thinking In the Literaturementioning
confidence: 99%
“…Prior work has also established the construct and predictive validity of the measure. For instance, prior work with the scale has revealed differences in how systems thinkers represent complex problems like environmental dilemmas (Davis and Stroink, ) and social issues (Thibodeau et al ., ) and approach problems that require creative thinking (Randle, ). Davis and Stroink (), for example, showed that systems thinkers were more likely to engage in pro‐environmental behaviour when presented with a complex environmental dilemma (Davis and Stroink, ).…”
Section: The Systems Thinking Scalementioning
confidence: 99%
“…Concurrently, Davis and Stroink worked to develop a survey‐based ‘Systems Thinking Scale’ (STS) designed to measure an individual's ‘tendency to perceive and understand relevant phenomena as emergent from complex, dynamic and nested systems’ (Davis and Stroink, ). In the STS assessment, the respondents rate their degree of agreement with 15 statements on a Likert scale.…”
Section: Introductionmentioning
confidence: 99%
“…Davis and Stroink used a sample of college students to compare their measure of systems thinking with several well‐established measures of cognitive and behavioural relationships to the environment including the Connectedness to Nature Scale (Mayer and Frantz, ), an Environmental Behavior Scale (Mayer and Frantz, ), the New Ecological Paradigm (Dunlap et al, ), the Environmental Motives Scale (Schultz, ), and the Marlow‐Crowne Social Desirability Scale (Crowne and Marlowe, ). They found that those who scored high in systems thinking had a stronger ecological world view and connection to nature and were more likely to engage in pro‐environmental behaviours than those who scored low (Davis and Stroink, ). Thibodeau et al () expanded on this work through surveys of adults in the USA drawn from a Mechanical Turk sample.…”
Section: Introductionmentioning
confidence: 99%